Obraz Rosji mikołajowskiej w Pamiętnikach św. Zygmunta Szczęsnego Felińskiego - Kościołek, Anna (Acta Polono-Ruthenica, 2018)
The memoirs of saint Zygmunt Szczęsny Feliński were written down during the archbishop’s stay in Jarosław, where he was sent in punishment for his defense of the rights of the Church and the Motherland. The works have played an important role in the history of Polish culture and literature. The article aims at depicting the Nicholas Russia, which the future archbishop had the opportunity to become well acquainted with during his studies in Moscow at the Łomonosow University and later on at the Roman Catholic Spiritual Academy in Petersburg. In his memoirs the author criticized the Russian Empire and noted its weak points, mainly bribery, the state of education, religious awareness and the condition of the Orthodox clergy.